The Development of an Augmented Reality Game KANJI Write for Beginners - Cai Xian Lai; Norshahila Ibrahim; Noor Hidayah Azmi; Erni Marlina Saari; Fadhlina Mohd Razali (Pejabat Karang Mengarang UPSI, 2021)
Learning how to write in Japanese is now a new trend in Malaysia, but Kanji is hard for non-native Japanese speakers to understand and memorize if not taught from young. Beginners who learn Kanji Japanese language faced difficulties in memorizing the kanji characters with correct stroke order. Thus, KANJI Write, an educational Augmented Reality (AR) adventure game was designed and developed to overcome the problem. The main purpose of the game is to help players memorizing the correct stroke order of Kanji characters through playing the game. Players will play as Nana, an Asian girl who has started learning Kanji and facing difficulties in memorizing Kanji stroke order. The art style of the game is following the direction of cuteness 3D low poly style. The most eye-catching point about this game is that the game level is activated by scanning the cards. After scanning those cards, players can start exploring and searching for the strokes needed to complete the level. A playtesting session was carried out and the result showed that KANJI Write successfully helped the players in memorizing the correct Kanji strokes order. The results also showed positive results in the game concept and the game visual. However, the game is still lacking in functionality and will be improved to increase the user experience rate.   Based on the findings of the study, it is recommended that: • KANJI write game could be a learning tool for UPSI students that can be used in Japanese language subjects under the Faculty of Languages and Communication. • Instead of numbers, other categories for example verbs, expressions, and nouns in JLPT N5 can be added as content into KANJI write. • The game can be improvised so that the player does not need the flash AR card to play the game.